IMPLEMENTASI METODE SINGLE EXPONENTIAL SMOOTHING DALAM PERAMALAN PENJUALAN MINUMAN BOBA - Sholikhatul Kasanah, Eka; Yuana, Haris; Nur Budiman, Saiful (Universitas Islam Balitar, 2022)
Many competitors and the impact of covid-19 caused sales of boba drinks to be erratic. This creates problems for Boba Tresnatea drink sellers because they cannot know that Boba drinks will increase or decrease in sales in the future. To prepare for this, forecasting is necessary. One method that can be used for forecasting is Single Exponential Smoothing (SES). SES was chosen because it is good for short-term forecasting. SES can be used to forecast or predict something in the future by utilizing data from the past, to help make decisions in the future so as to minimize existing risks. Forecasting results for August 2022 with an alpha of 0.8 is 388 cups and 0.9 is 390 cups. The results of the MAD test with an alpha of 0.8 is 40.09180147 and an alpha of 0.9 is 39.12510214. MAPE with an alpha value of 0.8 is 11.95645923 and an alpha value of 0.9 is 11.63512324. The best used alpha value is 0.9. The results of SES forecasting in this case are categorized as good because based on the feasibility index the value of 10% to 20% is declared good.